Peningkatan Kemampuan Pemahaman Konsep Penjumlahan Bilangan 1-10 melalui Media Pembelajaran Kubus Bilangan pada Siswa Kelas 1A SD Negeri 104202 Bandar Setia - Nur Wahyuni; Eva Nur Handayani (Lembag, 2024)
This study aims to improve the understanding of addition concepts of numbers 1-10 in first-grade elementary school students through the use of number cube learning media. The research method used is an experimental method with a pre-test and post-test design. The research subjects were first-grade students divided into two groups: an experimental group and a control group. The experimental group was taught using number cube learning media, while the control group was taught using conventional methods. Data were collected through tests of understanding the addition concepts of numbers 1-10 before and after learning. The results showed a significant increase in the understanding of addition concepts of numbers 1-10 in the experimental group that used number cube learning media compared to the control group. The use of number cubes provides a concrete and interactive visual representation, thus helping students understand the concept of addition more effectively. This indicates that number cube learning media is effective in improving the understanding of addition concepts of numbers 1-10 in first-grade students. This study recommends the use of number cube learning media as an innovative and effective alternative learning method to improve the understanding of mathematical concepts in young children. Further research can be conducted to investigate the effectiveness of number cube learning media on other mathematical materials and at different educational levels. In addition, further research is needed on the development of more varied and interesting number cube learning media for students.